Proposta de um guia de gerenciamento de desenvolvimento de produto para indústrias montadoras - Maffei, Alexandro (2014)
In this times, the technology s advances, the freedom and ease access to information, which eventually approaching markets to their consumers, whose choose who will provide a desired product or service. Therefore, this text will present a guide based in some concepts and methods as project management, concurrent engineering and DFMA. That will be a reference guide for the assembly s optimization in industries. So that this guide will provide the minimum precautions to be observed when developing a product, with special attention to the manufacturing and assembly process, as a competitive alternative for the companies to keep active and growing up, by the manufacturing and assembly process improvement, during the product development stage. Being the difference between ways of managing product design, thinking in manufacturing, spelled the end of the study, which will provide a SUGGESTION OF A MANAGEMENT GUIDE FOR PRODUCT DEVELOPMENT TO THE ASSEMBLY INDUSTRY.